2021
DOI: 10.1101/2021.09.29.462473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Odor motion sensing enables complex plume navigation

Abstract: Insects can detect bilateral differences in odor concentration between their two antennae, enabling them to sense odor gradients. While gradients aid navigation in simple odor environments like static ribbons, their role in navigating complex plumes remains unknown. Here, we use a virtual reality paradigm to show that Drosophila use bilateral sensing for a distinct computation: detecting the motion of odor signals. Such odor direction sensing is computationally equivalent to motion detection algorithms underly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…It is possible that in high-intermittency plumes organisms might use frequency to track the edges of odor plumes or even execute offset responses, such as those detailed in Álvarez-Salvado et al, 2018 . Moreover, it has recently been shown that flies can use bilateral information to detect the direction of motion of odor signals ( Kadakia et al, 2021 ), and that this information is particularly relevant in turbulent environments. In more diffuse and smooth plumes, odor velocity is less well-defined, and might be of more limited use.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in high-intermittency plumes organisms might use frequency to track the edges of odor plumes or even execute offset responses, such as those detailed in Álvarez-Salvado et al, 2018 . Moreover, it has recently been shown that flies can use bilateral information to detect the direction of motion of odor signals ( Kadakia et al, 2021 ), and that this information is particularly relevant in turbulent environments. In more diffuse and smooth plumes, odor velocity is less well-defined, and might be of more limited use.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fictive CO 2 delivered optogenetically was critical for studying the internal state of the mosquito after these transient host cues. Delivery and removal of real CO 2 necessitates constant air flow, which is itself an important sensory cue for insects ( Alvarez-Salvado et al, 2018 ; Kadakia et al, 2021 ; Suver et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the wealth of architectural insights emerging from the fly connectome may be used to constrain wiring motifs in artificial networks 72 . Modelling multiple antennae 36,73 , or more generally a biomechanical body, would enrich the interactions between the agent and the simulation environment 22,74 .…”
Section: Limitations and Future Workmentioning
confidence: 99%